Delayed hemolytic transfusion reaction presenting as a painful crisis in a patient with sickle cell anemia - Fabron Junior, Antonio; Moreira Junior, Gilberto; Bordin, José Orlando (São Paulo Medical Journal, 1999)
CONTEXT: Patients with sickle cell anemia (SCA) are frequently transfused with red blood cells (RBC). Recently, we reported that the calculated risk of RBC alloimmunization per transfused unit in Brazilian patients with SCA is 1.15%. We describe a delayed hemolytic transfusion reaction (DHTR) presenting as a painful crisis in a patient with SCA. CASE REPORT: A 35-year-old Brazilian female with homozygous SCA was admitted for a program of partial exchange transfusion prior to cholecystectomy. Her blood group was O RhD positive and no atypical RBC alloantibody was detected using the indirect antiglobulin technique. Pre-transfusional hemoglobin (Hb) was 8.7 g/dL and isovolumic partial exchange transfusion was performed using 4 units of ABO compatible packed RBC. Five days after the last transfusion she developed generalized joint pain and fever of 39°C. Her Hb level dropped from 12.0 g/dL to 9.3 g/dL and the unconjugated bilirrubin level rose to 27 mmol/L. She was jaundiced and had hemoglobinuria. Hemoglobin electrophoresis showed 48.7% HbS, 46.6% HbA1, 2.7% HbA2, and 2.0% HbF. The patient’s extended RBC phenotype was CDe, K-k+, Kp(a-b+), Fy(a-b-), M+N+s+, Le(a+b-), Di(a-). An RBC alloantibody with specificity to the Rh system (anti-c, titer 1:16.384) was identified by the indirect antiglobulin test. The Rh phenotype of the RBC used in the last packed RBC transfusion was CcDEe. The patient was discharged, asymptomatic, 7 days after admission.